Labour market integration programmes for refugees in Austria: Do they really work and for whom? - Isilda Mara (The Vienna Institute for International Economic Studies (wiiw), 2023)
In this study, we evaluate the effectiveness of the participation of refugees in integration programmes intended to help them gain employment. The specific programmes considered are the Competence Check programme and the Integration Year programme that were introduced in Austria around the time of the 2015 crisis, when refugees poured from the Middle East into the EU. The study is based on the fourth and fifth waves of a survey (FIMAS) of refugees from Afghanistan, Iraq, Iran and Syria in Austria, and it uses matching models to evaluate the effects on employment of participation in those two programmes. More specifically, it applies multivariate matching methods that ensure better balancing properties between the control and the treated groups. We find especially positive effects of the programmes on the employability of women, the poorly educated, younger and older age cohorts. These programmes thus seem to work specifically for those that find themselves in a more vulnerable labour market situation.
Keywords: J68; H43; C13; 330; refugees; matching methods; multivariate distance matching; labour market integration; labour market policies